Machine Learning and Artificial Intelligence Use in Marketing - Kim, Deageon; Hwang, Gi Hyun (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Business analytics, artificial intelligence, and machine learning can analyze and forecast customer behavior thanks to the abundance of transaction and demographic data. This increases customer happiness and boosts sales. Predictive analytics, for instance, use various algorithms to forecast the relationship between outcomes and factors and to spot data trends. Marketers study data trends using data mining techniques to forecast consumer interests. Marketers may now automate the pattern-searching and pattern-identification procedures to enable personalized and one-to-one marketing, delivering customized messages and product proposals to both current and potential clients. This analysis will concentrate on marketing efforts using AI and machine learning. Both an interview and a survey were used in this review. For the marketing and sales sector, it is crucial to research The Marketing Role of Artificial Intelligence and Machine Learning.